2005
DOI: 10.1590/s1806-37132005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Variações climáticas e uso de serviços de saúde em crianças asmáticas menores de cinco anos de idade: um estudo ecológico

Abstract: Objective: To study variations in climate (dry or rainy periods) and health services use for the treatment of asthma in children under five years of age. Methods: An ecological study was conducted and involved analysis of the medical charts of all children under the age of five that were diagnosed with asthma and treated in the Municipal Emergency Room of the city of Cuiabá, located in the state of Mato Grosso, Brazil. In accordance with the geographic location of Cuiabá, two climatic periods were identified: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
0
5
0
17
Order By: Relevance
“…As to seasons, contrary to what was expected, it was interesting to analyze the results, because it was found that, in emergency cases, there was a greater frequency of visits for bronchitis during fall/summer combined, the rainy season, in which the frequency was higher than in the dry season. The highest rate of lower respiratory tract infections in the emergency room found in the rainy season was possibly related to the excess moisture in the living environment of the child, due to heavy and constant rains, and the results could range from a simple cold to a more severe ARI (11) . In addition, children spend more time indoors and in contact with allergenic substances, which are more numerous in this period, due to a greater growth of fungi related to excessive moisture (12) .…”
Section: Discussionmentioning
confidence: 99%
“…As to seasons, contrary to what was expected, it was interesting to analyze the results, because it was found that, in emergency cases, there was a greater frequency of visits for bronchitis during fall/summer combined, the rainy season, in which the frequency was higher than in the dry season. The highest rate of lower respiratory tract infections in the emergency room found in the rainy season was possibly related to the excess moisture in the living environment of the child, due to heavy and constant rains, and the results could range from a simple cold to a more severe ARI (11) . In addition, children spend more time indoors and in contact with allergenic substances, which are more numerous in this period, due to a greater growth of fungi related to excessive moisture (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the assessments occurred in the month of October (springtime), exceptionally in the city of Belo Horizonte, at this time of the year, there was a sudden decrease in the temperature, with temperatures close to 17ºC, according to the National Meteorology Service. 20 According to Saldanha et al, 21 the influence of weather changes, particularly sudden decreases in temperature, are associated with a higher dispersion of aeroallergens. In this situation, asthma crises are more frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Os fatores ambientais que atuam sobre a asma, aumentando as suas taxas de morbidade e gravidade mais importantes são os poluentes no ar atmosférico, tanto externo quanto interno, e as condições meteorológicas do local, como a temperatura, a umidade relativa do ar e a velocidade dos ventos, que podem aumentar a duração da exposição aos poluentes e impedir sua dissipação 26,27 . O município de Uruguaiana não apresenta estas características industriais semelhantes às cidades de maior índice na prevalência de asma, muito embora apresente grandes alterações climáticas e amplitude térmica durante suas estações ou até mesmo no período de 24 horas, o que poderia aumentar a incidência de asma.…”
Section: -7 Anos (N=161) 13-14 Anos (N=230)unclassified